(untitled) (Baghdad Science Journal, 2018)
Study showed structure of pecten oculi in the Kestrel Falco tinnunculus L.wasPleated type and consisted of 17 folds which were thick. While in the Collared DoveStreptopelia decaocto F. was Vaned type and consisted of 13 folds and it describedthin. The illustrated histological study of pecten oculi folds in the Kestrel and theCollared Dove was composed of large number of capillaries, large blood vessels andpigment cells which were few in Kestrel compare with the Collared Dove. The bridgein the Kestrel and the Collared Dove pecten oculi was consisted of connective tissue,many pigment cells, and contains on little capillaries and it linked the membrane tothe internal limiting membrane of the retina in the Kestrel.Key words: birds, pecten oculi, morphology, histology